2016
DOI: 10.1158/2326-6066.cir-15-0104
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Soluble Tumor Necrosis Factor Prevents Chemically Induced Carcinogenesis in Mice

Abstract: Tumor necrosis factor (TNF) is a potent promoter of carcinogenesis and potentially important target for cancer prevention. TNF is produced as functionally distinct transmembrane and soluble molecules (tmTNF and sTNF, respectively), but their individual roles in carcinogenesis are unexplored. We investigated the participation of tmTNF and sTNF in chemically induced carcinogenesis in mice. We found that injection of XPro1595, a dominant-negative TNF biologic (DN-TNF) and specific antagonist of sTNF, decreased tu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 48 publications
0
38
0
Order By: Relevance
“…To investigate in detail how LGALS1 was involved in the GBM immunosuppressive microenvironment, we undertook big data analysis and evaluated the immunosuppressive cytokines known to be tightly associated with immunosuppressive microenvironment. LGASL1 was positively associated with immunosuppressive genes: LGALS3 , impairing function of human CD4 and CD8 tumour‐infiltrating lymphocytes, SWAP70 restricting spontaneous maturation of dendritic cells (DCs), CHI3L1 secreted by M2 macrophages promoting gastric and breast cancer metastasis, CCL2, SERPING1 inhibiting activation of the complement system, ANXA1 regulating TGF‐β signalling and promoting metastasis formation of basal‐like breast cancer cells, SHC1 promoting breast cancer immune suppression through STAT1 and STAT3, TIMP1 having a liner relationship with CD11b + Gr1+ myeloid cells and CD4 + CD25 + FOXP3+ Tregs, ICAM1 critical for mesenchymal stem cell (MSC)‐mediated immunosuppression, LTBP1 required for an adequate TGF‐β function, CD163, MR1 resulting in a relative increase in Tregs and TNFRSF1A required for STAT3 phosphorylation and MDSC accumulation . We also found that the expression of VEGFA, CCL2 and TGF‐β were restrained in the LGALS1 knockdown group.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate in detail how LGALS1 was involved in the GBM immunosuppressive microenvironment, we undertook big data analysis and evaluated the immunosuppressive cytokines known to be tightly associated with immunosuppressive microenvironment. LGASL1 was positively associated with immunosuppressive genes: LGALS3 , impairing function of human CD4 and CD8 tumour‐infiltrating lymphocytes, SWAP70 restricting spontaneous maturation of dendritic cells (DCs), CHI3L1 secreted by M2 macrophages promoting gastric and breast cancer metastasis, CCL2, SERPING1 inhibiting activation of the complement system, ANXA1 regulating TGF‐β signalling and promoting metastasis formation of basal‐like breast cancer cells, SHC1 promoting breast cancer immune suppression through STAT1 and STAT3, TIMP1 having a liner relationship with CD11b + Gr1+ myeloid cells and CD4 + CD25 + FOXP3+ Tregs, ICAM1 critical for mesenchymal stem cell (MSC)‐mediated immunosuppression, LTBP1 required for an adequate TGF‐β function, CD163, MR1 resulting in a relative increase in Tregs and TNFRSF1A required for STAT3 phosphorylation and MDSC accumulation . We also found that the expression of VEGFA, CCL2 and TGF‐β were restrained in the LGALS1 knockdown group.…”
Section: Discussionmentioning
confidence: 99%
“…The soluble form of TNFa (sTNFa) mainly triggers TNFR-I, whereas the transmembranous form (tmTNFa) preferentially activates TNFR-II (50) with distinct biological functions. It has been documented that mainly sTNFa drives the differentiation and accumulation of MDSCs in a MCA tumor model (14). The function of TNFa in the regulation of hematopoiesis has been analyzed in different models with partially contradictory results: TNFa has been shown to suppress or increase the colony formation capacity of HSCs and their in vivo reconstitution capacity, probably depending on the dose and length of exposure studied (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, GM-CSF-secreted by mammary 4T1 tumors led to the expansion of myeloid progenitors and accumulation of CD11b þ GR-1 þ myeloid cells (12). In addition, TNFa has been shown to lead to the accumulation of MDSCs in murine and human tumors (13,14). Importantly, the vast majority of solid tumors do not secrete hematopoietic cytokines (8).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned before, TNFα is a major mediator of inflammation (59) with ambiguous effects and has been detected in human ovarian (60)(61)(62), breast (62,63), endometrial (62), oral (64), pancreatic (65), gastric (66), liver (67), prostate, bladder and colorectal (68) cancer as well as in lymphomas (69) and leukemias. It has been reported that knockout mice for TNFα are resistant to chemical-induced carcinogenesis (70)(71)(72). There has been quite a big controversy regarding TNFα expression as a parameter to predict clinical outcome in breast cancer patients (73)(74)(75)(76).…”
Section: The Relevance Of Tnfα In Cancermentioning
confidence: 99%